Intercalation of Methylene Blue in a High-Charge Calcium Montmorillonite — An Indication of Surface Charge Determination - Zhaohui Li; Chih-Jen Wang; Wei-Teh Jiang (Adsorption Science & Technology)
The suitability and applicability of using Methylene Blue (MB), a cationic dye, for cation-exchange capacity (CEC) and specific surface area (SSA) determinations has been studied extensively. Although many workers have reported satisfactory results between the CEC determined by the MB method and other methods, large discrepancies among CEC values determined by different methods are also found in the literature. The work reported herein was focused at elucidating the interlayer configuration of adsorbed/intercalated MB in SAz-1, a high-charge montmorillonite, using MB adsorption, exchangeable cation desorption, counterion (Cl − ) adsorption, X-ray diffraction (XRD) and Fourier-transform infrared (FT-IR) analyses. A complete balance between the amount of MB cation adsorbed and that of exchangeable cations desorbed at a 1:1 charge ratio for MB uptake by SAz-1 indicated that cation-exchange was the most important mechanism in this case together with supplementary hydrogen bonding. The adsorbed MB molecules associated into dimers and were orientated in the interlayer in a nearly vertical configuration, with the sulphur atom keyed onto the surface. In a vertical orientation, the MB dimer occupies a projected area of 120–130 Å 2 , similar to the surface area of 130 Å 2 previously assumed from SSA determinations for the horizontally aligned MB molecule. Hence, it is the charge density rather than the horizontal configuration of the MB molecules that controls the MB adsorption capacity. As such, the CEC determination of swelling clays using the MB adsorption method is justified. However, SSA determination by the MB method is correct only if the charge density is less than the projected area of 120–130 Å 2 for an MB dimer. This suggests that the previous assumption of the adsorption of a horizontally orientated MB molecule onto the surface of clay minerals is questionable.